Induction of cytokines via NF-κB and p38 MAP kinase signalling pathways associated with the immunomodulation by Lactobacillus plantarum NDC 75017 in vitro and in vivo. (January 2016) - Jiang, Yujun; Li, Li; Sun, Haoxiu; Shan, Yi; Liu, Ying; Li, Liang; Qu, Bo; Man, Chaoxin
Highlights: Lactobacillus plantarum NDC 75017 induced IL-1β, IL-6 and TNF-α expression in Caco-2 cells and intestines. The NF-κB and p38 MAPK pathways were involved in the cytokine's transient expression stimulated by Strain NDC 75017. Strain NDC 75017 has potential immunoregulatory effects on the host. The scientific basis for the use of Strain NDC 75017 in functional foods was preliminarily explained. Abstract: Lactobacillus has been used as a functional food ingredient to improve health. The expression of the pro-inflammatory cytokines interleukin-1β (IL-1β), IL-6 and tumour necrosis factor-α (TNF-α) stimulated by Lactobacillus plantarum NDC 75017 were investigated in the Caco-2 cells and intestinal tract of mice. In vitro, three cytokines (IL-1β, TNF-α, IL-6) could be momentarily induced; increased to the maximum level at 2, 4 and 8 h, respectively; and then decreased. Similar regulation could also be observed in vivo, and the expression of all cytokines peaked on day 5. Moreover, a transient activation of toll-like receptors (TLRs) and phosphorylation of NF-κB p65 and p38 MAPK were detected in Caco-2 cells by stimulation of NDC 75017. Inhibitors of NF-κB and p38 MAPK significantly suppressed cytokine expression ( P  < 0.01). Results suggested that L. plantarum NDC 75017 could perform a beneficial immunomodulation involving the pro-inflammatory cytokines NF-κB and p38 MAPK. This strain could be applied as a new potential immunoregulatory agent in functional foods.